Perencanaan Kinerja Komite Penjamin Mutu BPSDM Provinsi Jawa Barat - Pertiwi, Bella Ayu (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
National Institute of Public Administration command to all of the Governmenttraining institution to form The independent team of Quality Assurance Committee. The aim of this study is to describe the performance planning model of the quality assurance committee team based on the quality model from Juran’s Trilogy. A qualitative approach was used in this study. The result of this study proves that the QAC Team of BPSDM West Java Province has carried out performance planning (Bacal) according to the stages. The model used as a reference is the quality model of the Juran’s Trilogy. The model is almost the same as Robert Bacal’s performance planning. However, the disadvantage is that there are no performance indicators that shows the benefits and impact of implementating quality assurance.